2022
DOI: 10.17721/fujcv10i2p9-21
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Health Risk Assessment of Potentially Toxic Elements in Medicinal Herbs from Northern Nigeria

Abstract: The concentrations of potentially toxic elements (Fe, Cd, Pb, Cu, Ni, Cr, and Zn) in most consumed medicinal herbs in Northern Nigeria were analyzed using Atomic Absorption Spectrometry (AAS). Twenty medicinal herbs were selected and purchased from the local markets. The findings of the study revealed that the investigated herb samples contained considerable levels of elements; Cu, Fe, Pb, Cd, and Cr above the permissible limits. The health risk observed as hazard index (HI) indicated that values were >1, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(40 reference statements)
0
1
1
Order By: Relevance
“…However, compared with the background values of the world average for soil, the mean concentrations of the investigated PTEs were lower than the world average elemental values [32]. The PTE concentrations observed in this study are lower than those reported outside Nigeria [29,[33][34][35] and in Nigeria [19][20][21]36], but in comparable with those at Karst, Brazil [37], Odajana, Nigeria [28], and Canakale-Ezine, Turkey [39] presented in (Table 2), which indicate that cement production activities had less in uence in the study areas. Moreover, it has been reported that an estimation of adverse health effects associated with PTEs, based on concentrations is not su cient and must be followed with other estimated indices [16].…”
Section: Concentrations Of Pte Occurrence In Soilscontrasting
confidence: 77%
See 1 more Smart Citation
“…However, compared with the background values of the world average for soil, the mean concentrations of the investigated PTEs were lower than the world average elemental values [32]. The PTE concentrations observed in this study are lower than those reported outside Nigeria [29,[33][34][35] and in Nigeria [19][20][21]36], but in comparable with those at Karst, Brazil [37], Odajana, Nigeria [28], and Canakale-Ezine, Turkey [39] presented in (Table 2), which indicate that cement production activities had less in uence in the study areas. Moreover, it has been reported that an estimation of adverse health effects associated with PTEs, based on concentrations is not su cient and must be followed with other estimated indices [16].…”
Section: Concentrations Of Pte Occurrence In Soilscontrasting
confidence: 77%
“…Moreover, studies of PTE concentrations and risk assessment on soils have been reported in Nigeria [12,[18][19][20][21]. However, limited or no study have been reported on geochemical, and risk assessments of the PTE study area.…”
Section: Introductionmentioning
confidence: 99%